The Impossibility of Mere Animal Knowledge for Reflective Subjects - Goldberg, Sanford; Matheson, Jonathan (Erkenntnis, 2020)
In this paper we give reasons to think that reflective epistemic subjects cannot possess mere animal knowledge. To do so we bring together literature on defeat and higher-order evidence with literature on the distinction between animal knowledge and reflective knowledge. We then defend our argument from a series of possible objections.